From Internal Migration to International Migration in Mexico. Notes on the Formation of a Field of Study - Liliana Rivera Sánchez (Íconos)
This article offers a panoramic view of Mexico regarding some of its contributions in studies about internal migration to the fieldwork of international migration. Specifically, the contributions of this field to studies on migration between Mexico and the United States of America are reviewed. Throughout this text, a selective analysis is made on some studies that contributed to the explanation of the construction and maintenance - over time and despite geographical distance - of social links, as well as the various modalities of continuity, social and economic solidarity, between migrants and their families.